Multimedia content security in cloud environments using asymmetric cryptography - Ali, Najma Imtiaz; Brohi, Imtiaz Ali; Jamali, Mujeeb-Ur-Rehman; Emran, Nurul A.; Shah, Syed Sohail Ahmed; Arain, Mazhar Basheer; Jamali, Aadil; Jhanjhi, Noor Zaman (Edelweiss Applied Science and Technology, 2026)
Information security and cybersecurity involve protecting personal identifiable information and confidential data stored in the cloud. System vulnerabilities are heightened due to increased processing capabilities. The demand for multimedia content stored in cloud environments is growing, raising significant security concerns, particularly regarding unauthorized access to sensitive information. This study offers a posteriori analysis of various asymmetric algorithms tested with small, medium, and large datasets. The analysis reveals the efficiency and limitations of these algorithms, providing valuable insights for selecting appropriate security measures. Notably, Elliptic Curve Cryptography (ECC) with specific key curve parameters demonstrates superior efficiency, shorter key lengths, and adaptability to resource constraints, making it well-suited for cloud-based multimedia applications. Ensuring the protection of private and confidential data through cryptographic solutions that are resilient to evolving cyber threats is crucial in the dynamic cloud environment. The findings contribute to enhancing content security by applying modern cryptographic techniques within cloud infrastructure. These results will aid researchers and decision-makers in choosing effective algorithms to secure multimedia content stored in the cloud, ultimately strengthening data protection and privacy in cloud computing systems.